2022
DOI: 10.1021/acs.iecr.2c01713
|View full text |Cite
|
Sign up to set email alerts
|

Control of Asphaltene Deposition by Chemical Inhibitors in Calcite Pore: Molecular Dynamics Approach

Abstract: Asphaltene deposition is a major problem during oil production and transportation that imposes extra treatment costs and reduces oil production. Historically, various chemical inhibitors have been developed to resolve the asphaltene deposition issue. However, the inhibitors are usually effective for a specific type of crude oil and asphaltene since asphaltene's nature is different for various oil samples. To develop a proper chemical inhibitor, the interaction between the inhibitor and asphaltene needs to be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…For instance, the periodic boundary conditions need to be removed using “ gmx trajconv ” and “ -pbc whole ” function, and any molecules except the target molecules subjected to aggregate or deposit, asphaltene in our case, need to be eliminated from the box. The accuracy and reliability of the scripted code were verified in our previous papers. , …”
Section: Simulation Strategymentioning
confidence: 69%
See 1 more Smart Citation
“…For instance, the periodic boundary conditions need to be removed using “ gmx trajconv ” and “ -pbc whole ” function, and any molecules except the target molecules subjected to aggregate or deposit, asphaltene in our case, need to be eliminated from the box. The accuracy and reliability of the scripted code were verified in our previous papers. , …”
Section: Simulation Strategymentioning
confidence: 69%
“…The accuracy and reliability of the scripted code were verified in our previous papers. 66,82 The code considers asphaltenes to be aggregated if the closest atom of two adjacent asphaltenes is less than 0.35 nm (the value is reported in the literature). 45 From the prediction of aggregates, the code can measure the average aggregation number, aggregate size, and aggregate density.…”
Section: Simulation Strategymentioning
confidence: 99%
“…Besides the experimental investigation, the theoretical calculation of molecular simulation (MS) can be utilized as an available method to allow direct observations of the interfacial phenomenon. With the rapid development of information technology, the MDS method has become a powerful tool to explore and reveal interaction mechanisms at the molecular scale in a wide range of conditions. , A series of studies have been reported on the interfacial investigation of asphaltene, including asphaltene precipitation in CO 2 flooding by Fang et al, the control of asphaltene deposition by chemical inhibitors in calcite pores by Ghamartale et al, the diffusion and distribution of asphaltene on a quartz surface by Wu et al, C5Pe adsorption configurations on silica surfaces by Ji et al, and calcite–organic molecule–water interaction mechanism by Chai et al Hence, MDS methods can serve as useful tools to provide microscopic findings to confirm the macroscopic experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is not observed for octyl phenol, whose main interaction with asphaltenes is through hydrogen bonding. This group also studied the influence of the same ionic liquid on deposition of asphaltenes over calcite pores 17 and concluded that, although the IL additive reduced the faceto-face aggregation of asphaltenes, it did not prevent deposition because it was unable to form a barrier layer near the calcite surface due to its short alkyl side chain. In both cases, the only solvent tested was n-heptane, which is a challenging test for the additive but not the solvent environment that best mimics crude oil.…”
Section: Introductionmentioning
confidence: 99%